Analisis Kesulitan Pendidik Dalam Mengimplementasikan Penilaian Autentik Kurikulum 2013 Di SD PAB 12 Sampali - Abyena Hafza; Isal Salbila; Karfika Suci Ramadani; Risma Handayani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
In 2013 the 2013 Curriculum was implemented which changed the assessment of students both in terms of knowledge, attitudes and skills. One of the focuses of the 2013 curriculum is authentic assessment. Based on the results of observations and interviews that researchers conducted with several teachers, many teachers experienced difficulties in conducting authentic assessments in the 2013 curriculum, namely teachers felt that Authentic Assessment was too complicated because there were too many aspects to be assessed. The purpose of this study is to analyze the difficulties of teachers in implementing authentic assessment in the 2013 Curriculum, describe teacher constraints and efforts made by teachers. This study used descriptive qualitative method. The data collection techniques used are document studies, observations, and interviews. The results showed that teachers still have difficulty in implementing authentic assessments of the 2013 curriculum, in this case teachers have difficulty